Prediction Model of Balanced Nutrition Practices among University Students in the COVID-19 Outbreak - Indah, Yusma; Ansyar, Dian Ihwana; Ibrahim, Irviani Anwar; Suyuti, Syarfaini; Hartini, Diah Ayu; Dewi, Nikmah Utami (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: Students included in the category of youth need balanced nutrition practices, especially during the COVID-19 outbreak. This study aims to determine the model of balanced nutrition behavior in youth in Gowa Regency, Makassar, Indonesia. MATERIALS AND METHODS: This study was a quantitative study with a cross-sectional study, in which primary data were collected from June to July 2020. The respondents were 597 students at public and private universities located in Gowa Regency who filled the questionnaires. RESULTS: The bivariate analysis results, which were based on the respondents’ characteristics, showed that only age significantly affected balanced nutrition practices (p = 0.048). Based on the independent variables studied, poor knowledge (p = 0.000, ORcrude = 2.229 [CI 1.601–3.105]) and poor attitude (p = 0.001, ORcrude = 1.735 [CI 1.250-2.409]) obtained a significant correlation with poor balanced nutrition practices. The final model of balanced nutrition practices using multivariate analysis indicated that knowledge was the biggest predictor of balanced nutrition (p = 0.000, OR = 2.067 [CI 1.476–2.893]). The number implied that respondents with good knowledge had 2.067 times the opportunity to take balanced nutrition practices than those with less knowledge after controlling for age and attitude variables. CONCLUSION: Producing well-balanced nutrition behavior requires well-balanced nutrition knowledge, including university students who belong to the late adolescent stage.